(untitled) (Journal of Applied Learning and Teaching, 2022)
Objective: Evaluate the role of flipped class in an undergraduate epidemiology course. Methods: A pre-post quasi-experiment with historical controls was conducted to evaluate students’ attitude, perception, and self-efficacy of epidemiology through a flipped class approach. Results: The sample included 254 undergraduate students. Students’ attitude, perception, and the usefulness of epidemiology, along with self-efficacy in problem solving, significantly changed after end of class. The average grade rose from B to A-. Qualitative feedback captured two themes: increased pace of the course and collaborative learning. Conclusion: To encourage collaborative learning, this study encourages the integration of active learning together with the traditional lecture style.